Perbandingan Efek Larvasida Minyak Atsiri Daun Cengkeh (Syzygium aromaticum L.) Varietas Zanzibar dengan Temephos terhadap Larva Nyamuk Aedes aegypti - Pamungkas, Ridzmullah Wishnu; Syafei, Neneng Syarifah; Soeroto, Arto Yuwono (Pharmaceutical Sciences and Research, 2016)
The use of temephos as larvicides in disease prevention Dengue Hemorrhagic Fever (DHF) in Indonesia has been going on for 40 years. Larviciding very long led the resistance to temephos. Cloves, one of native Indonesia plant contains eugenol that are toxic to the insect’s body. This study aims to examine the effectiveness of Zanzibar clove leaf essential oil compared to temephos in killing the larvae of Aedes aegypti. This study uses experimental laboratory research design. The samples are larvae of Aedes aegypti stage III. The mosquito larvae were classified into six groups, each given a clove leaf essential oil with different concentrations. Next will be observed the number of larvae that die after 24 hours. Based on statistical test p-value p < 0.05 it indicates there are differences in the average mortality in the test group, and post hoc analysis showed the test group with 100 ppm of essential oil is not a significant difference with temephos. This study suggests the essential oil of clove leaf varieties of Zanzibar has the same effectiveness with temephos in killing the larvae of Aedes aegypti.